IMPLEMENTASI KEBIJAKAN DALAM PROSES BELAJAR DAN MENGAJAR DI MIN 1 PEKANBARU: IMPLEMENTASI KEBIJAKAN PENDIDIKAN - harianto, aisyah (JURNAL ISLAMIKA, 2023)
Implementation of policies in the teaching and learning process is an important step to ensure that the policies that have been set can be implemented properly in the school environment. In implementing these principles, teachers have an important role both in teaching subjects and in guiding and advising students. In guidance and counseling services, alternative steps must be implemented in the form of assistance based on problems and backgrounds. Guidance and counseling teachers must use different approaches and techniques in providing assistance so that the activities carried out are successful. If the desired success is not achieved, guidance and counseling can be repeated. The principle must be followed that students are given the opportunity to tackle their own problems. Teachers or mentors play an important role in considering various topics with students and helping them make decisions.